Discrete approach for flow field designs of parallel channel configurations in fuel cells - Wang, Junye; Wang, Hualin (International journal of hydrogen energy, 2012)
It is the major challenge to transform a laboratory scale production of fuel cells to an industrial scale one and to meet the requirements of throughput, operating life, low cost, reliability and high efficiency in R&D of fuel cells. Designs of uniform flow distribution are central to upscale fuel cells as well as to tackle critical issues of water, thermal and current management. However, in spite of our growing appreciation of designs of uniform flow distribution, there is little or no practical solution to ensure a uniform flow distribution across channels of a cell and cells of a stack in designs of flow fields. The purpose of this paper was to develop a discrete approach to find a design that met requirements of flow distribution uniformity and pressure drop in parallel channel configurations with Z-type arrangement through adjustments of configurations and normalised structural parameters. Variation of the frictional and the momentum coefficients with flow velocities was incorporated into the flow distribution equation to improve modelling accuracy. We also developed procedure, measures and guideline for the designs of flow distribution and pressure drop to bridge knowledge gap between the generalised theory and industrial applications. The results showed that the present approach could provide the practical guideline to evaluate quantitatively performance of different layout configurations, structures, and flow conditions. ► Development and use of discrete approach for designs of flow fields in fuel cells. ► Quantitative assessment of uniformity of flow distribution and pressure drops. ► Systematic approach to find a design that meets flow uniformity and pressure drop. ► Procedure, measures and guideline how to achieve uniform flow distribution. ► Sensitivity analysis of flow coefficients.